Update to the ASFA guidelines on the use of therapeutic apheresis in ANCA‐associated vasculitis. Issue 5 (7th August 2020) - Balogun, Rasheed A.; Sanchez, Amber P.; Klingel, Reinhard; Witt, Volker; Aqui, Nicole; Meyer, Erin; Padmanabhan, Anand; Pham, Huy P.; Schneiderman, Jennifer; Schwartz, Joseph; Wu, Yanyun; Zantek, Nicole D.; et al.
Abstract: Since 1986, the American Society for Apheresis (ASFA) has published practice guidelines on the use of therapeutic apheresis in the Journal of Clinical Apheresis (JCA) Special Issue. Since 2007, updated guidelines have been published every 3 years to reflect current evidence based apheresis practice with the most recent edition (8th) published in 2019. With each edition, the guidelines are reviewed and updated based on any newly published literature since the last review. The PEXIVAS study, an international, randomized controlled trial comparing therapeutic plasma exchange (TPE) vs no TPE and standard vs reduced dose steroid regimen on the primary composite outcome of end stage renal disease or death in patients with ANCA‐associated vasculitis (AAV), was published in February 2020. This study represents the largest study on the role of therapeutic apheresis in AAV published to date and prompted the JCA Special Issue Writing Committee to reassess the current AAV fact sheet for updates based on this newly available evidence. This interim fact sheet summarizes current ASFA recommendations for the evidence‐based use of therapeutic apheresis in AAV and supersedes the recommendations published in the 2019 guidelines.